COMMUNITY STRUCTURE OF GASTROPODS ON THE INTERTIDAL ZONE AT KASIAK ISLAND NORTH PARIAMAN WEST SUMATERA PROVINCE - Astuti Marnis; Thamrin Thamrin; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT             This research was conducted in July 2019in the Kasiak Island North Pariaman of West Sumatera Province.The aims of the study were to analyze the is to know the structure of gastropod community which includes the type, diversity.uniformity, dominancy, and distribution of gastropods that are found in the intertidal zones of the Kasiak Island North Pariaman West Sumatera Province.The method used in this research is the survey method. Determining the point of sampling location is purposive sampling consisting of 3 stations. Each station is divided into 3 transects and each transects consists of 3 plots. At the research site found 168 individuals belonging to 4 orders, 7 families and 12 species. Abundance of gastropods ranged from 12,66 to 29,33 ind/m2. The average Diversity Index (H') was 2,33 indicating moderate diversity; the average Dominance Index (C) was 0,72 indicating that no spesies dominates the site and the Diversity Index (E) was 0,26 indicating the uniformity of organisms in a balanced state.The distribution pattern (Id) ranges from 1,19 to 1,25 indicatinggastropods distribution in group'sKeywords:gastropods, intertidal zone, community structure